2018
DOI: 10.1021/acsami.8b09242
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Green Synthesis of Ultrabright N-Doped Fluorescent Silicon Nanoparticles for Cellular Imaging by Using Ethylenediaminetetraacetic Acid Disodium Salt as an Effective Reductant

Abstract: Because of excellent photoluminescence properties, robust chemical inertness, and low cytotoxicity of silicon nanoparticles (Si NPs), exploration of their applications in bioimaging is of great interest. Up to date, a method to synthesis Si NPs with high fluorescence quantum yield (QY) is still challenging. This situation limits the further applications of Si NPs. In this work, we report a mild, simple, and green one-pot method to synthesis N-doped fluorescent Si NPs with an ultrahigh QY up to 62%, using ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…The emission wavelength of the as-prepared SiNPs remained almost unchanged (Figure 4) at excitation wavelengths ranging from 300 to 430 nm and 600 to 850 nm, which suggested that the as-synthesized SiNPs exhibited wavelength-independent emission behavior and excellent up-conversion fluorescence. These results were consistent with those of previous studies [59,60].…”
Section: Optical Characterizations Of Sinpssupporting
confidence: 94%
“…The emission wavelength of the as-prepared SiNPs remained almost unchanged (Figure 4) at excitation wavelengths ranging from 300 to 430 nm and 600 to 850 nm, which suggested that the as-synthesized SiNPs exhibited wavelength-independent emission behavior and excellent up-conversion fluorescence. These results were consistent with those of previous studies [59,60].…”
Section: Optical Characterizations Of Sinpssupporting
confidence: 94%
“…The full survey of XPS scan displays three typical peaks (Figure S6, Supporting Information): C 1s (285 eV), N 1s (400 eV), and Si 2p (102 eV), which indicates that the three composites are consisted of the same elements . In the high‐resolution scans (Figure S7, Supporting Information), the C 1s band can be deconvoluted into six peaks at 283.5, 284.6, 285.4, 286.4, 287.2, and 288.7 eV, corresponding to CSi, CC, CN, CO, CO, and OCO, respectively . The N 1s band contains three peaks at 398.8, 399.7, and 400.9 eV, representing NSi, CNC, and NH, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…In the high‐resolution scans (Figure S7, Supporting Information), the C 1s band can be deconvoluted into six peaks at 283.5, 284.6, 285.4, 286.4, 287.2, and 288.7 eV, corresponding to CSi, CC, CN, CO, CO, and OCO, respectively . The N 1s band contains three peaks at 398.8, 399.7, and 400.9 eV, representing NSi, CNC, and NH, respectively . The Si 2p band can be deconvoluted into three peaks at 100.7, 101.8, and 102.6 eV for SiC, SiN, and SiO, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…A lack of cytotoxicity has also been reported for laser-synthesized SiQDs [34]. Other workers have shown some cytotoxicity of biogenic Si/SiO2 particles in the A431 human epithelial cell line after 3 h of exposure to concentrations >1 mM [35] and recently a decrease in viability (MTT assay) at 500 mg mL1 of nanoparticles prepared by reduction of N -[3-(trimethoxysilyl)propyl]ethylenediamine [36]. The surface chemistry of these particles was very different to the present alkyl SiQDs (oxide vs alkyl), nevertheless it was important to extend the cytotoxicity studies to higher concentrations and longer duration exposures and in the relevant cell line, CACO-2.…”
Section: Resultsmentioning
confidence: 93%